2016
DOI: 10.1038/ejhg.2016.162
|View full text |Cite
|
Sign up to set email alerts
|

Limb girdle myasthenia with digenic RAPSN and a novel disease gene AK9 mutations

Abstract: Though dysfunction of neuromuscular junction (NMJ) is associated with congenital myasthenic syndrome (CMS), the proteins involved in neuromuscular transmission have not been completely identified. In this study, we aimed to identify a novel CMS gene in a consanguineous family with limb-girdle type CMS. Homozygosity mapping of the novel CMS gene was performed using high-density single-nucleotide polymorphism microarrays. The variants in CMS gene were identified by whole-exome sequencing (WES) and Sanger sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Moreover, in some cases, mutations in more than one gene could be necessary to cause the disease [ 42 ]. Thus, digenic inheritance has been proven for a subtype of facioscapulohumeral muscular dystrophy [ 43 ] found in congenital myasthenic syndrome [ 44 ], and it has also been suggested for calpainopathy [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some cases, mutations in more than one gene could be necessary to cause the disease [ 42 ]. Thus, digenic inheritance has been proven for a subtype of facioscapulohumeral muscular dystrophy [ 43 ] found in congenital myasthenic syndrome [ 44 ], and it has also been suggested for calpainopathy [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al reported that defective of AK9 reduces N-glycosylation of AChR and rapsyn while a defective RAPSN impairs the clustering of AChR. 38 Thus, we speculated RAPSN and the methylation of RAPSN connected with LC through CDK5 by cell cycle and AK9 by N-glycosylation pathway. Still, the specify molecular mechanism of RAPSN methylation and LC might be a topic for further studies as well.…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, typical digenic inheritance has been demonstrated in facioscapulohumeral muscular dystrophy (Lemmers et al 2012), in congenital myasthenic syndrome (Lam et al 2017), and in calpainopathy (Sáenz and accumulation of seemingly benign variants, including both mutations and polymorphisms, can lead to disease. In c and d, variants cause partial defects either in one pathway or in intersecting pathways, which together produce a cumulative effect leading to the disease.…”
Section: Potential Non-monogenic Inheritancementioning
confidence: 99%